Polityka rodzinna prowadzona w środowiskach lokalnych - Drejer, Fryderyk (Karkonoska Państwowa Szkoła Wyższa, 2011)
Due to its status as a basic social unit the family retains numerous rights guaranteed by appropriate documents of international character. In all the documents legal and economic protection is mentioned, which is to be provided to the family by the state and the society. It is the basic condition of proper functioning of the family within the society and its positive changes. Every family under pressure from various outside factors undergoes manifold changes, which are not always positive. The family is, therefore, to be provided with such conditions as not to allow for crises, often constituting a source of dysfunctions and pathologies. It is the fundamental aim of government family politics realised by local environments.
Keywords: rodzina; opieka; polityka rodzina; środowisko lokalne